Faktor Risiko Dermatitis pada Anak yang Datang Berobat ke UPTD Puskesmas Penyandingan Kabupaten OKU - Eva Yustati; Eichi eptiani; Maya Sartika (Jurnal Kesehatan Saelmakers PERDANA, 2023)
Dermatitis is a chronic, residive skin disease that often occurs in infants, children and adults. Various studies state that the prevalence of dermatitis is increasing every year so that it becomes a major health problem. Based on data for the 10 most common diseases obtained from the OKU District Health Office, the proportion of dermatitis in 2020 was 2,992 cases (17.9%). UPTD Puskesmas Penyandingan, in 2020 the proportion of dermatitis was 227 cases (14.4%). This study aims to determine the risk factors for dermatitis in children who come for treatment to the UPTD Puskesmas Pengandingan, OKU Regency in 2021. The research design used was Cross Sectional. The population is all pediatric patients who seek treatment at the UPTD of the Puskesmas Penyandingan, OKU Regency, based on visit data from January to March 2021 totaling 246 children, so the average monthly visit is 82 children. The statistical test used is the chi square test. Based on univariate analysis, there were 29 (35.4%) children suffering from dermatitis, 54 (65.9%) respondents with clean water quality met the requirements, 56 (68.3%) respondents with good personal hygiene and 50 respondents with good personal hygiene. (61%) respondents with clean environmental sanitation. The results of the bivariate analysis showed that there was a significant relationship between clean water quality and the incidence of dermatitis in children with p value 0.001, there was a significant relationship between personal hygiene and the incidence of dermatitis in children with p value 0.002 and there was a significant relationship between environmental sanitation and the incidence of dermatitis. in children p value 0.001. There is a significant relationship between the quality of clean water, personal hygiene and environmental sanitation with the incidence of dermatitis in children